Anti-Haptic Experience: A Critical Analysis of the Role of the Sense of Touch - Matt Teismann (Oz, 2008)
Does the tangible man-made object represent haptic experience or an illusion of it—what role does the object play in hapticity? A system of expectations tells us that the haptic experience is intrinsic to the object which instigates it.